MYC paralog-dependent apoptotic priming orchestrates a spectrum of vulnerabilities in small cell lung cancer - Marcel A. Dammert (Nature Portfolio, 2019)
The expression of oncogenic MYC paralogs in small cell lung cancer is mutually exclusive. In this study, the authors show that MYC, but not MYCN or MYCL, represses BCL2, resulting in cells that are uniquely sensitive to apoptosis, and find that CHK1 and AURKA inhibitors may be useful for treating these cancers.